Gender and School Level in Relation to Homework Behavior, Intrinsic Motivation, and Parental Involvement - Avcı, Süleyman; Özgenel, Mustafa; Avcu, Akif; Özgenel, Mustafa (John Wiley and Sons Inc, 2025)
The objective of this study is to investigate the influence of gender and school level (middle and high school) on a range of homework-related behaviors and attitudes among students. The study's participants were 920 students from various middle and high school levels in Turkey. The study examined a number of variables, including homework completion, homework time, academic achievement, and intrinsic motivation. The findings of the study indicated that middle school students received a higher volume of homework, completed more homework, and exhibited greater intrinsic motivation than high school students. Female students demonstrated higher academic achievement and intrinsic motivation than male students at both middle and high school levels. Additionally, parental autonomy support was a significant predictor at the middle school level but declined at the high school level, while male students exhibited greater levels of parental control.
Keywords: Gender; Homework behaviors; Intrinsic motivation; Parental homework involvement; School level